The Role of Transparency on the Effect of Leverage on Company Value - Firmansyah Firmansyah; Meutia Layli (Master of Accounting Universitas Trunojoyo Madura, 2023)
The company’s value can provide welfare to investors if the cost of bidding also increases; the cost of shares of an organization, the higher the welfare assistance from investors. This study aims to test and analyze the role of transparency moderation on company value and leverage. The method used in this study is a quantitative method with secondary data. The data collection technique uses purposive sampling. The data analysis is in the form of annual financial statements on manufacturing companies listed on the IDX for the 2018 – 2020 period. This research method uses multiple linear regression analysis. The results showed that leverage had a significant positive effect on the company’s value. Meanwhile, company transparency does not affect the company value, but the company's transparency can moderate the relationship between the variable leverage to the Company Values. This illustrates that easy information access is one of the indicators of the company's transparency in conveying its information to parties outside the company.